Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/oby.20027
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive thermogenesis with weight loss in humans

Abstract: Adaptive thermogenesis (AT) with weight loss refers to underfeeding-associated fall in resting and nonresting energy expenditure (REE, non-REE); this is independent of body weight and body composition. In humans, the existence of AT was inconsistently shown and its clinical significance has been questioned. Objectives: Discrepant findings are mainly due to different definitions of AT, the use of various and nonstandardized study protocols, and the limits of accuracy of methods to assess energy expenditure. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 97 publications
4
117
0
1
Order By: Relevance
“…45 As such, further research is needed to establish the biological basis of adaptive thermogenesis in humans. 44 Taken together, the metabolic effects observed in the present study are generally in agreement with what has been reported in weight-loss interventions in overweight and obese populations as well as in observational studies in anorexia nervosa patients, although weight loss was much less than expected, even after accounting for differences in the composition of weight loss and potential lack of compliance. This discrepancy suggests that other metabolic adaptations unique to normal-weight women may prevent them from becoming underweight.…”
Section: Metabolic Adaptationssupporting
confidence: 92%
See 1 more Smart Citation
“…45 As such, further research is needed to establish the biological basis of adaptive thermogenesis in humans. 44 Taken together, the metabolic effects observed in the present study are generally in agreement with what has been reported in weight-loss interventions in overweight and obese populations as well as in observational studies in anorexia nervosa patients, although weight loss was much less than expected, even after accounting for differences in the composition of weight loss and potential lack of compliance. This discrepancy suggests that other metabolic adaptations unique to normal-weight women may prevent them from becoming underweight.…”
Section: Metabolic Adaptationssupporting
confidence: 92%
“…Adaptive thermogenesis is considered to be a result of the downregulation of cellular thermogenesis via uncoupling protein 1 and other mechanisms, primarily in the liver and skeletal muscle, and changes in T3, leptin and sympathetic nervous system have been considered as the primary drivers of adaptive thermogenesis. 44 In support of this, we found that T3 and leptin closely mirrored changes in RMR adjusted for fat-free mass, which is also in agreement with data from anorexia nervosa patients, in whom T3, leptin and RMR are chronically suppressed, but return to normal levels following refeeding and weight gain. 22,25 Although parallel changes in T3, leptin and RMR have also been reported in normal-weight men undergoing calorie-restricted weight loss and subsequent refeeding, it is noteworthy that neither changes in T3 or leptin nor sympathetic nervous system activity predicted the magnitude of adaptive thermogenesis in this population.…”
Section: Metabolic Adaptationssupporting
confidence: 90%
“…Thus, insights on defective responses to HFD are essential to identify effective therapeutic targets against obesity. Prevalent studies in this direction mainly focus on nutrient surplus or partitioning in key metabolic tissues (1,5,6). Our data showed that HFD feeding increased cAMP, glycolysis, and ATP in rbc; raised blood O 2 level; and increased diet-induced EE, revealing -to our knowledge -a novel mechanism involving SNS→ rbc→ O 2 supply as part of the pathway underlying HFD-induced EE.…”
Section: Discussionmentioning
confidence: 76%
“…While nutrient flux and metabolism in key metabolic tissues have been major research focuses (1,5,6), a potential direct contribution of defective O 2 supply to obesity development has largely been neglected. In this regard, a subtle change in O 2 supply may affect mitochondrial metabolism, which may ultimately lead to a considerable alteration in body weight (7).…”
Section: Introductionmentioning
confidence: 99%
“…Although this phenomenon is likely driven, at least in part, by neuroendocrine adaptations to caloric imbalance, its underlying molecular mechanisms are not yet fully elucidated (1). Because adaptive thermogenesis intensifies and is sustained over time as weight loss increases (2,3), it is considered to mitigate weight loss.…”
mentioning
confidence: 99%